Survey on public key encryption with equality test - Yuanhao WANG; Hongbo LI; Yuzhao CUI; Qingwen GUO; Qiong HUANG (网络与信息安全学报)
As one of the important methods of solving the problem of computation over encrypted data under multiple public keys in cloud environment,public key encryption with equality test (PKEET) supports to check whether two ciphertexts encrypted under (possibly) different public keys contain the same message without decrypting the ciphertexts.Definitions,security models and six types of authorization modes of PKEET are introduced and summarized.Besides,the relationship between PKEET and public key encryption with keyword search (PKES) is discussed.Several typical public-key,identity-based and attribute-based encryption with equality test schemes proposed recently are analyzed and compared.Furthermore,some application scenarios and research directions are discussed.